Relationship component of supplier involvement in New Product Development (NPD) process - (:unkn) unknown (My University, 2006)
As developing the right product at the shortest time to the market at the right quality level and price is a necessity due to shortening of product life cycle, and increased global competition, close interaction of the supplier with the customer increases new product development efficiency. Existence of relationship components, communication, commitment and trust, is very important for the close interaction of the supplier with the customer. An effective supplier involvement in the new product development process decreases the complexity of the development process and avoids suppliers manufacturing and technological constraints. The main objective is to match the supplier capabilities with the customer requirements. This is only possible with close relationship between the supplier and customer. The study emphasize importance the relationship between the supplier and the customer; the effect of the relationship on the supplier involvement in the new product development process. (c) 2006 PICMET.